2021
DOI: 10.3390/ma14040719
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Mechanical Properties of a-BCN Films Prepared by an Arc-Sputtering Hybrid Process

Abstract: Amorphous boron carbon nitride (a-BCN) films exhibit excellent properties such as high hardness and high wear resistance. However, the correlation between the film structure and its mechanical properties is not fully understood. In this study, a-BCN films were prepared by an arc-sputtering hybrid process under various coating conditions, and the correlations between the film’s structure and mechanical properties were clarified. Glow discharge optical emission spectroscopy, X-ray photoelectron spectroscopy, Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…It should be emphasized that these hardness values are higher than that of polycrystalline h-BN powder (H = 0.05-0.6 GPa) [103]. A significant decrease in the values of H and E compared to LPCVD films is associated with the dominance of "softer" sp 2 B-N and sp 2 B-C-N bonds and a smaller number of B-C bonds [3,104,105]. The presence of hydrogen-and oxygen-containing bonds also contributed to the decrease in values of mechanical performances [52].…”
Section: Mechanical Propertiesmentioning
confidence: 95%
“…It should be emphasized that these hardness values are higher than that of polycrystalline h-BN powder (H = 0.05-0.6 GPa) [103]. A significant decrease in the values of H and E compared to LPCVD films is associated with the dominance of "softer" sp 2 B-N and sp 2 B-C-N bonds and a smaller number of B-C bonds [3,104,105]. The presence of hydrogen-and oxygen-containing bonds also contributed to the decrease in values of mechanical performances [52].…”
Section: Mechanical Propertiesmentioning
confidence: 95%
“…Panjan et al [50] revealed that post-polishing procedures for cathodic arc-deposited TiN coatings could improve the wear resistance and shorten the running-in duration. Another interesting fabrication method is the combined vacuum arc and magnetron sputtering hybrid process described by Hirata et al [51], as shown in Figure 3d, for creating amorphous boron carbon nitride (a-BCN) films for tribological applications. Here, the BN target is mounted on the RFMS, while the graphite target is positioned on the cathodic arc gun to deposit the films.…”
Section: Fabrication Methodsmentioning
confidence: 99%
“…Moreover, the diagonal placement of the arc gun in relation to the substrate allows for better control of droplet deposition in the coatings, a common problem associated with conventional vacuum arc processes. [45], (b) ultra-short PLD [46], (c) FCVA [49], and (d) arc-sputtering hybrid method [51]. (Reproduced with permission.…”
Section: Fabrication Methodsmentioning
confidence: 99%
“…C film and a wear resistance superior to that of the a-C film (Hirata, et al, 2021). Diamondlike carbon-silver composite films possess sufficient hardness and Young's modulus values.…”
Section: Introductionmentioning
confidence: 94%